2020
DOI: 10.1002/adsc.202000202
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Copper‐Catalyzed Radical Ring‐Opening Cyanation of Cyclopropanols and Cyclopropanone Acetals

Abstract: A novel approach for enantioselective cyanation of cyclopropanols and their derivatives through copper-catalyzed radical relay processes has been developed. Various cyclopropanols and cyclopropanone acetals are compatible to the catalytic conditions, providing β-carbonyl nitriles with excellent enantioselectivity. These products can be readily converted to chiral γ-amino acids derivatives and drugs such as (R)-baclofen. Preliminary mechanistic studies have supported a ring-opening process for cyclopropanoxy ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…In view of the electrophilic properties of iminyl CN bonds, we envisioned that nucleophilic carbon radicals might serve as a good coupling partner. Previous reports, including our work, indicated that nucleophilic carbon-centered radicals could be efficiently generated via the radical ring-opening of cyclopropanols. Herein, we report a novel Ag-catalyzed formal [3 + 2] cycloaddition reaction using cyclopropanols as a C3 subunit and imines as a two-atom subunit, in which a wide range of polysubstituted pyrroles can be efficiently synthesized from readily attained starting materials under mild conditions (Scheme c).…”
supporting
confidence: 51%
“…In view of the electrophilic properties of iminyl CN bonds, we envisioned that nucleophilic carbon radicals might serve as a good coupling partner. Previous reports, including our work, indicated that nucleophilic carbon-centered radicals could be efficiently generated via the radical ring-opening of cyclopropanols. Herein, we report a novel Ag-catalyzed formal [3 + 2] cycloaddition reaction using cyclopropanols as a C3 subunit and imines as a two-atom subunit, in which a wide range of polysubstituted pyrroles can be efficiently synthesized from readily attained starting materials under mild conditions (Scheme c).…”
supporting
confidence: 51%
“…Scheme 50 Oxidative ring-opening of cyclopropanone ketals with MnO 2 or PbO 2 for the synthesis of -alkoxy esters, -acetoxy esters, or -amino esters In 2020, Liu, Guo, and co-workers reported an enantioselective ring-opening cyanation of cyclopropanone alkyl silyl ketals 209 through a copper-catalyzed radical relay strategy in the presence of TMSCN and N-fluorobenzenesulfonimide (NFSI) as stoichiometric oxidant (Scheme 51). 78 Optically active -cyano esters 210 were obtained in moderate to good yields with a high level of stereocontrol when 1-aminoindan-2-ol-derived bis(oxazoline) (1S,2R)-L* was employed as chiral ligand. Mechanistic studies including radical trapping experiments have shown that the transformation proceeds via the homolysis of a Cu(II)-cyclopropanoxide complex, leading to a transient oxygen radical 211 capable of rapid ring-opening to a -radical intermediate 212, once again selectively cleaving the most substituted C1-C2 bond due to increased stability of the resulting benzylic radical.…”
Section: Review Synthesismentioning
confidence: 99%
“…32 Other examples that should operate by a radical mechanism include intramolecular ring-opening cyclization onto an iminium ion to give a bridged azacycle 33 and enantioselective oxidative ring-opening cyanation of 2-aryl cyclopropanol derivatives with trimethylsilyl cyanide. 34 Meanwhile, Wang and coworkers reported CuI-catalyzed ringopening alkylation of cyclopropanols with α-diazoesters, which was proposed to involve ring-opening nucleophilic addition of the β-position of the cyclopropanol to an electrophilic coppercarbene complex (Scheme 21b). 35 Scheme 21.…”
Section: Scheme 18mentioning
confidence: 99%